EDUCATIONAL METHODOLOGY: UTILIZING SONGS AND MUSIC TO INSTRUCT ENGLISH TO STUDENTS WHO ARE LEARNING THE LANGUAGE AS A FOREIGN LANGUAGE - Dilrabo Safarova Kholmurodovna (Web of Journals Publishing, 2024)
Even though there are many ways to teach the English language, one of the most effective ways is teaching through educational songs and music. Many teachers already know that teaching English through songs brings joy to the learning process. For this reason, appropriate teaching strategies are invented to help the learners while learning with songs. Therefore, this article aims to explore the importance of songs for students who learn English as a second language.
Keywords: syntax, vocabulary, EFL students grammar, context, comprehension, listening, speaking, fluency, rhythms, stress, music, motivation, confidence, attract students’ attention.